Palabos: Parallel Lattice Boltzmann Solver. (1st January 2021) - Latt, Jonas; Malaspinas, Orestis; Kontaxakis, Dimitrios; Parmigiani, Andrea; Lagrava, Daniel; Brogi, Federico; Belgacem, Mohamed Ben; Thorimbert, Yann; Leclaire, Sébastien; Li, Sha; Marson, Francesco; Lemus, Jonathan; et al.
Abstract: We present the scope, concepts, data structures and application programming models of the open-source Lattice Boltzmann library Palabos. Palabos is a C++ software platform developed since 2010 for Computational Fluid Dynamics simulations and Lattice Boltzmann modeling, which specifically targets applications with complex, coupled physics. The software proposes a very broad modeling framework, capable of addressing a large number of applications of interest in the Lattice Boltzmann community, yet exhibits solid computational performance. The article describes the philosophy of this programming framework and lists the models already implemented. Finally, benchmark simulations are provided which serve as a proof of quality of the implemented core functionalities.